FACTORS ASSOCIATED WITH HIGH-RISK DISCHARGES FROM NURSING FACILITIES. (20th December 2022) - Hughes, Kelly; Feng, Zhanlian; Oliveira, Iara
Abstract: Although some nursing facility discharges are appropriate or an individual's choice, others may be facility-initiated discharges (FIDs) that are potentially inappropriate. Since FIDs cannot be observed directly in available data, this study focused on live discharges of residents with risk factors for FIDs from 2011-2017. We defined risk factors as characteristics identified in prior literature that were more prevalent among residents discharged live than residents not discharged in our analysis. We found the following risk factors: severe behavioral symptoms; impairments requiring more staff time; and transition to Medicaid eligibility. Psychiatric and mood disorders were not identified in prior literature but also associated with live discharge. Risk factors were consistent across years but varied by state and facility type. For-profit, chain, and government facilities were most likely to discharge residents with risk factors. Furthermore, the rates of post-discharge acute care use were highest among residents with risk factors.